2016
DOI: 10.12983/ijsras-2016-p0084-0098
|View full text |Cite
|
Sign up to set email alerts
|

Farming Households’ Environment, Nutrition and Health Interplay in Southwest, Nigeria

Abstract: The pervasive implication of environmental and socioeconomic challenge(s) poses serious threat to nutritionalhealth and agricultural sustainability in Nigeria. This study adopts the UNICEF's conceptual framework of undernutrition to investigate factors influencing farming households' nutrition and the determinants of health status in the Southwestern part of Nigeria. The results presented here relied on data collected on households' environmental, socioeconomic , nutrition and health profile through multistage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…This might be true as the increase in age of participants might translate into more experience which invariably translates into higher income. This corroborates with existing studies indicating earnings increases with increasing age, specialized skill trainings, and/or education of the household heads [58][59][60]. In addition, the results also show that marital status of the household head was positively and significantly related to income (p < 0.05).…”
Section: Determinants Of Household's Income: Ols Regressionsupporting
confidence: 91%
“…This might be true as the increase in age of participants might translate into more experience which invariably translates into higher income. This corroborates with existing studies indicating earnings increases with increasing age, specialized skill trainings, and/or education of the household heads [58][59][60]. In addition, the results also show that marital status of the household head was positively and significantly related to income (p < 0.05).…”
Section: Determinants Of Household's Income: Ols Regressionsupporting
confidence: 91%
“…More so, the educational status of the farming households' head shows that 43.10% of the pooled respondents have secondary education with mean years of education of 9.28 years. The implication of these results is that higher number educational year could have a positive influence on the ability of the farmers to know their nutrition composition of food and the need for diversity ( Omotayo, 2016b ).…”
Section: Resultsmentioning
confidence: 99%
“…Empirical studies have shown that households in developing countries are unable to sustain current levels of consumption during and after severe health crises due to substantial increase in medical expenditure and/or loss of income ( Wagstaff and Lindelow, 2010 ; Sparrow et al., 2014 ; Alam and Mahal, 2014 ; Nguyen et al., 2020 ). Health events are also found to have an adverse impact on nutritional status and educational attainment of household members ( Dhanaraj, 2016 ; Omotayo, 2016a ). Health shocks, whether an event of death or disease, can cause significant adverse economic outcomes for households in low- and middle-income countries (LMICs).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The access to competitive health care system has drastically declined due to the high rate of poverty and deprivation in Nigeria. The weak economic stability in the country has affected various sectors of the economy including the health sector leading to low productivity, poor service delivery and poor health outcomes ( Omotayo, 2016a , 2020 ). The Nigerian health sector is still striving to provide basic health care services with the collaborative efforts of the three tiers of government but efforts to achieve this seem impracticable due to the current state of the economy ( Eko, 2017 ).…”
Section: Introductionmentioning
confidence: 99%